Financial Behavior of Workers Under Work from Home Scheme during the Global Energy Crisis - Astuti; Tiara Adhitya; Uchi Qadri; Mahdanisa Hasibuan (Penerbit Jurnal Indonesia, 2026)
The ongoing global energy crisis has led to a substantial increase in household utility expenses, placing additional financial strain on individuals, particularly those engaged in remote work. This study investigates the role of financial literacy and perceived energy cost pressure in shaping the financial behavior of employees working from home during a period of economic instability. The research adopts a quantitative associative design, involving 100 formal sector workers operating under a remote work arrangement. Data were collected through structured questionnaires and analyzed using multiple linear regression techniques. The findings reveal that financial literacy positively influences financial behavior, while energy cost pressure exerts a significant negative effect. Together, both variables explain 42.8% of the variance in financial behavior. These results suggest that financial capability functions as a key adaptive resource in responding to external cost pressures. The study underscores the need to strengthen financial awareness and institutional support to sustain household financial stability in evolving work conditions.